Antibacterial Effectiveness Test Of Kersen Leaf Extract Lotion (Muntingia Calabura L.) Against Staphylococcus Aureus Using Disc Diffusion Method - Sofiyatun Nisa; Riana Putri Rahmawati; Bintari Tri Sukoharjanti (CV. Inara, 2025)
Increasing antibiotic resistance, especially in Staphylococcus aureus, has prompted the search for safer and more effective antibacterial alternatives. Cherry leaves (Muntingia calabura L.) can be used as an antibacterial and contain secondary metabolites flavonoids, alkaloids, and tannins. This study aims to formulate an ethanol extract of cherry leaves in the form of an antibacterial lotion and evaluate its effectiveness against Staphylococcus aureus using the disc diffusion method. This study used a laboratory experimental design with concentrations of ethanol extract of cherry leaves of 5%, 10%, and 15%. The antibacterial effectiveness test was carried out by measuring the growth inhibition zone of Staphylococcus aureus. Evaluation of the physical quality of the lotion included organoleptic tests, homogeneity, pH, spreadability, and viscosity to ensure the stability of the formulation. The irritation test was carried out using the patch test method for 24 hours to assess the safety of using the lotion on the skin. The results of the study on F1 showed an inhibition zone of 10.67 mm, an inhibition zone on F2 of 11 mm, an inhibition zone on F3 of 11.33 mm and in the positive control had an inhibition zone of 12.67 mm. The most optimal concentration in inhibiting the growth of Staphylococcus aureus bacteria was at concentration F3 (15%).